Life satisfaction, health, self-evaluation and sexuality in current university students of sport sciences, education and natural sciences - Martin Sigmund; Jana Kvintová; Hana Hřebíčková; Michal Šafář; Dagmar Sigmundová (Palacký University Olomouc, 2014)
Background: Lifestyle and health of an individual are influenced by many factors; a significant factor is life satisfaction. Life satisfaction is understood as a multidimensional construct closely related to the area of personal wellbeing and quality of life. Life satisfaction in university students represents one of the determinants of good health, high motivation for studying, work productivity, satisfactory interpersonal relationships and overall healthy lifestyle. Objective: The main objective of the present study is to identify and compare the level of overall life satisfaction and selected components of health, self-evaluation and sexuality in current university students with respect to their study specialization. Methods: The study included a total of 522 students from Palacký University. These were students from the Faculty of Physical Culture (n = 118), Faculty of Education (n = 218) and Faculty of Science (n = 186). In terms of age, the study focused on young adults aged 19 to 26. To assess the current level of life satisfaction, the research study used a standardized psychodiagnostic tool - Life Satisfaction Questionnaire (LSQ). The used diagnostic methods are fully standardized and contain domestic normative values. Statistical result processing was conducted using the Statistica programme v10.0. Results: The highest level of overall life satisfaction was revealed in university students of sport sciences. In comparison with the students of education and students of natural sciences the difference is significant. Satisfaction with health among the students of sport sciences is significantly higher than in the students of education (p ≤ .001; d = 0.53) and the students of natural sciences (p ≤ .05; d = 0.38). Similar results were found in the area of satisfaction with own person and self-evaluation, where the values of the students of sport sciences were significantly higher compared with the students of education (p ≤ .001; d = 0.39) and the students of natural sciences (p ≤ .001; d = 0.30). In the area of sexuality we revealed significantly higher values in the students of sport sciences compared with the students of natural sciences (p ≤ .05; d = 0.32). Conclusion: The results of the present study indicated that current university students who study sports sciences assess their life satisfaction significantly higher compared with the students of other specializations. The results of the study indicated a positive correlation between physical activity of current university students and the subjectively perceived level of life satisfaction, health, self-evaluation and sexuality.